El teatro infantil y su incidencia en el desarrollo del lenguaje de los niños y niñas de preparatoria, primer grado de educación básica del centro educativo Cristiano Bautista de la ciudad de Santo Domingo de los Tsáchilas. Periodo lectivo 2013 – 2014 - Escobar Villafuerte, Jenny Marilu (2014)
In the present research work called: CHILD THEATER AND ITS IMPACT ON LANGUAGE DEVELOPMENT OF CHILDREN OF SCHOOL, FIRST DEGREE OF BASIC EDUCATION OF SCHOOLS "CRISTIANO BAUTISTA" THE CITY OF SANTO DOMINGO DE TSÁCHILAS. LECTIVO PERIOD 2013-2014. This research has the general objective: To determine the incidence of the Children's Theatre in the Language Development of Children of School, First Grade Basic Education School "Cristiano Bautista" in the city of Santo Domingo de los Tsáchilas. The methods and techniques used for data collection and data analysis were: the Scientific, Deductive, Inductive, Analytical Synthetic, and Statistical Model method, the same that were used to explain the impact of the Children's Theatre in the development of language. As techniques were applied: a survey of teachers in order to learn about the activities of the Children's Theatre in the daily work ; and Observation Guide, in order to assess the language development of children from School, First Grade Basic Education School "Cristiano Bautista" in the city of Santo Domingo de los Tsáchilas. According to the results of the survey of teachers is determined that 100 % engaged in Children's Theatre once a week; and the types of plays that children use in their activities are the classic tales and puppetry. To the extent that we give more room within the institutional educational environment to children's theater, we will be including a major education and development of children aspect. The Children's Theatre opens the door to the creation, the story and history. The experiences of consciousness, attention, vision and hearing, provide an artistic and cultural wealth children. With the implementation of the Observation Guide to children of the School, it is concluded that 22% represent his character clearly equivalent to Very Satisfactory, 47% to represent your character do not clearly equivalent to Satisfactory; and 31% do not represent what your character is Little satisfactory.